Comparative study of the nutritional characteristics and fatty acid profiles of the seeds and seed oils of sweet, bell and bird varieties of pepper (capsicum species) - Adeyeye, A; Salami-Adeniyi, AI; Sulaiman, WK (International Journal of Advanced Chemistry, 2021)
The proximate compositions of the seeds and fatty acid contents of the seed oils of the three varieties of Capsicum (pepper) species fruits â€“ sweet, bell and bird pepper â€“ have been determined using standard AOAC methods. Their proximate compositions gave moisture contents as 82.54%, 83.32% and 84.74% for bird, sweet and bell peppers respectively. Other proximate values in the various pepper samples ranged as follows: crude fat 1.52%â€“2.21%, crude protein 2.64%â€“3.51%, crude fibre 2.72%â€“4.71%, ash contents 1.62%â€“3.03% and carbohydrate contents 4.52â€“6.96%. The order of abundance of the fatty acids were linoleic > oleic > stearic > palmitic in each sample. All the other fatty acids, except myristic acid in bell pepper seed oil, had values lower than 1.00% in all samples. The total unsaturated fatty acids predominated the total saturated ones with values ranging from 79.23% in bird pepper to 82.33% in bell pepper. The total polyunsaturated fatty acids ranged from 57.80% in sweet pepper to 66.50% in bell pepper while the total essential fatty acids ranged from 57.78% in sweet pepper to 66.00% in bell pepper. The total unsaturated/saturated (P/S) ratio was highest in bell pepper, making it the most nutritionally useful of them all.Â Â Â